DISSOLUTION DU SUJET ET SPECULARITE MINERALE DANS LA POETIQUE DE ROGER CAILLOIS - MOLL, François (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Dissolution of the Subject and Mineral Specularity in the Poetics of Roger Caillois. Heir to analogical thought – which is a scientific, philosophical and poetic thought of nature – Roger Caillois develops a demanding poetic ethics. Postulating, in his critical and poetic work, the necessary dissolution of the subject, Caillois only seeks to strengthen his presence, to ward off his fear of indistinction and to ensure, ultimately, his own scriptural legitimacy. In doing so, he chooses stone, which he opposes to the indecent volubility of the plant, as a literary model of sustainability, as the emblem of his poetics and as a lyrical mirror through which alone he agrees to appear in his own text. Article history: Received 20 April 2022; Revised 29 August 2022; Accepted 30 August 2022; Available online 20 September 2022; Available print 30 September 2022. REZUMAT. Disolutia subiectului și specularitate minerală în opera poetică a lui Roger Caillois. Promotor al gândirii analogice – o gândire științifică, filozofică și poetică a naturii – Roger Caillois dezvoltă o etică poetică extrem de exigentă. Postulând, în opera sa critică și poetică, necesitatea dizolvării subiectului, Caillois urmărește totodată să reconfirme prezența eului poetic, să-și alunge teama de instinct și să-și asigure, în cele din urmă, propria legitimitate literară. Procedând astfel, alege piatra, văzută mereu în opoziție cu volubilitatea indecentă a plantei, drept model literar al durabilului. Piatra va deveni atât o emblemă a poeticii lui Caillois, cât și un spațiu de reflectare a eului liric. Cuvinte-cheie: Caillois, poezie, natură, disoluție, subiect